Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/wnf.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Levodopa in Patients With Parkinson Disease and Motor Fluctuations Depending on the Presence of Helicobacter pylori Infection

Abstract: The H. pylori infection in PD patients with motor fluctuations, despite not significantly influencing PK parameters of LD and 3-OMD, may still have important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…They showed that the t max and C max were lower in HP negative patients while the AUC o was larger in the HP positive groups. They concluded that these differences may potentially have important clinical implications to the patient [24] . Their findings may thus help explain the significant differences in the baseline UPDRS and PDQ39 scores between our H. pylori - positive and negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the t max and C max were lower in HP negative patients while the AUC o was larger in the HP positive groups. They concluded that these differences may potentially have important clinical implications to the patient [24] . Their findings may thus help explain the significant differences in the baseline UPDRS and PDQ39 scores between our H. pylori - positive and negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have reported that gastric Helicobacter pylori infection is a factor contributing to motor fluctuations, and that improvement in consistency of l ‐dopa effect occurs once the infection is eradicated . However, a recent study of l ‐dopa pharmacokinetics in PD patients both with and without Helicobacter pylori infection does not confirm that disposition of l ‐dopa is necessarily changed by presence of the infection . Another factor interfering with l ‐dopa uptake and associated with motor fluctuations is bacterial overgrowth occurring in the small intestine.…”
Section: L‐dopa Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Remarkably, H. pylori uses levodopa in vitro as a growth supplement in an iron-restricted medium [ 34 ], suggesting H. pylori converts this phenylalanine/tyrosine derivative into a functional amino acid for its metabolism. Thus, the pharmacokinetics of levodopa may be altered by H. pylori , though the mechanism is not well understood [ 35 ].…”
mentioning
confidence: 99%